Nociceptor Neurons are Involved in the Host Response to Escherichia coli Urinary Tract Infections - Gao Z; Liu Y; Zhang L; Yang Z; Lv L; Wang S; Chen L; Zhou N; Zhu Y; Jiang X; Shi B; Li Y (Journal of Inflammation Research, 2022)
Zhengdong Gao,1,2,* Yaxiao Liu,1,2,* Lekai Zhang,1,2 Zizhuo Yang,1,2 Linchen Lv,1,2 Shuai Wang,1,2 Lipeng Chen,1,2 Nan Zhou,1,2 Yaofeng Zhu,1 Xuewen Jiang,1 Benkang Shi,1,2 Yan Li1,2 1Department of Urology, Qilu Hospital of Shandong University, Jinan, People’s Republic of China; 2Key Laboratory of Urinary Precision Diagnosis and Treatment in Universities of Shandong, Jinan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Benkang Shi; Yan Li, Department of Urology, Qilu Hospital of Shandong University, 107 Wenhuaxi Road, Jinan, 250012, People’s Republic of China, Email bkang68@sdu.edu.cn; yanli@sdu.edu.cnPurpose: Urinary tract infections (UTIs) can evoke a rapid host immune response leading to bladder inflammation and epithelial damage. Neuroimmune interactions are critical for regulating immune function in mucosal tissues. Yet the role of nociceptor neurons in bladder host defense has not been well defined. This study aimed to explore the interaction between nociceptor neurons and bladder immune system during UTIs.Methods: In this study, whether uropathogenic Escherichia coli (UPEC) and lipopolysaccharide (LPS) can directly stimulate nociceptor neurons was detected. Female C57BL/6J mice were treated with high dose of capsaicin, a high-affinity TRPV1 agonist, to ablate nociceptor neurons. Bladder inflammation, barrier epithelial function and bladder immune cell infiltration were assessed after UPEC infection. The level of neuropeptide calcitonin gene-related peptide (CGRP) in infected bladder was detected. Furthermore, the effects of CGRP on neutrophils and macrophages were evaluated both in vitro and in vivo.Results: We found that UPEC and its pathogenic factor LPS could directly excite nociceptor neurons, releasing CGRP into infected bladder, which suppressed the recruitment of neutrophils, the polarization of macrophages and the killing function of UPEC. Both Botulinum neurotoxin A (BoNT/A) and BIBN4096 (CGRP antagonism) blocked neuronal inhibition and prevented against UPEC infection.Conclusion: The present study showed a novel mechanism by which UPEC stimulated the secretion of CGRP from nociceptor neurons to suppress innate immunity.Keywords: UTIs, CGRP, nociceptor neurons, UPEC, innate immune cells